Men's and women's response to treatment and perceptions of outcomes in a randomized controlled trial of injectable opioid assisted treatment for severe opioid use disorder - Heather Palis; Kirsten Marchand; Daphne Guh; Suzanne Brissette; Kurt Lock; Scott MacDonald; Scott Harrison; Aslam H. Anis; Michael Krausz; David C. Marsh; Martin T. Schechter; Eugenia Oviedo-Joekes (BMC, 2017)
Abstract Background To test whether there are gender differences in treatment outcomes among patients receiving injectable opioids for the treatment of long-term opioid-dependence. The study additionally explores whether men and women have different perceptions of treatment effectiveness. Methods This study is a secondary analysis from SALOME, a double-blind, phase III, randomized controlled trial testing the non-inferiorirty of injectable hydromorphone to injectable diacetylmorphine among 202 long-term street opioid injectors in Vancouver (Canada). Given this was a secondary analysis, no a priori power calaculation was conducted. Differences in baseline characteristics and six-month treatment outcomes (illicit heroin use, opioid use, crack cocaine use, non-legal activities, physical and psychological health scores, urine positive for street heroin markers, and retention) were analysed by gender using fitted models. Responses to an open ended question on reasons for treatment effectiveness were explored with a thematic analysis. Results Men and women differed significantly on a number of characteristics at baseline. For example, women were significantly younger, presented to treatment with significantly higher rates of prior month sex work (31.5% vs. 0%), and used significantly more crack cocaine (14.71 vs. 8.38 days). After six-months of treatment there were no significant differences in treatment outcomes by gender, after adjusting for baseline values. For both men and women, improved health and quality of life were the most common reasons provided for treatment effectiveness, however women were more specific in the types of health improvements. Conclusions Despite presenting to treatment with vulnerabilities not faced to the same extent by men, at six-months women did not differ significantly from men in tested trial efficacy outcomes. While the primary outcome in the trial was the reduction of illicit opioid use, in the open-ended responses both men and women focused their comments on improvement in health and quality of life as reasons for treatment effectiveness. The supervised model of care with injectable medications provides a particularly suitable framework for providing care to opioid-dependent men and women not attracted or retained by other treatments. The absence of statistical differences reported in this secondary analysis may be due to lack of adequate statistical power to detect meaningful effects. Trial registration This trial is registered with ClinicalTrials.gov (NCT01447212) Registered: October 4, 2011 at the following link: https://clinicaltrials.gov/ct2/show/NCT01447212 .